Parental Height and Weight Influence Offspring Adiposity at 2 Years; Findings from the ROLO Kids Birth Cohort Study - Donnelly, Jean M.; Walsh, Jennifer M.; Horan, Mary K.; Mehegan, John; Molloy, Eleanor J.; Byrne, David F.; McAuliffe, Fionnuala M. (American Journal of Perinatology, 2021)
Objective The perinatal period and in utero environment are important for fetal growth, development, and fetal programming. This study aimed to determine the effect of parental anthropometry and the maternal metabolic milieu on offspring adiposity at 2 years of age.Study Design This longitudinal birth cohort includes analysis of maternal (n = 337) and paternal (n = 219) anthropometry and maternal and fetal metabolic markers (n = 337), including glucose, homeostatic model of assessment (HOMA), C-peptide, and leptin from participants of the ROLO (the Randomized Control Trial of Low) pregnancy study, and their partners, to determine an association with offspring anthropometry at two years of age.Results Linear regression, when adjusted for confounders, indicated maternal and paternal anthropometry and was associated with offspring weight and length at 2 years of age. Maternal height was negatively associated with general adiposity in the total cohort of children (p = 0.002) and in female children (p = 0.006) and central adiposity in the total child cohort (p < 0.001). Paternal height was also negatively associated with general adiposity in all children (p = 0.002) and central adiposity in total (p = 0.023) and female children (p = 0.008). Maternal glucose, insulin resistance, and fetal C-peptide positively correlated with anthropometry in total, male, and female children.Conclusion Parental anthropometry in the perinatal period has a long-lasting effect on offspring anthropometry beyond the neonatal period. Maternal and fetal metabolic factors influence adiposity, and this extends beyond the perinatal period. Parental adiposity may play a significant role in early childhood adiposity and may be a target for interventions to decrease the risk of early childhood obesity.Key Points
Keywords: maternal anthropometry; paternal anthropometry; adiposity; follow-up study